Does the optimization of a company's environmental performance reduce its systematic risk? New evidence from European listed companies. (14th February 2020) - Djoutsa Wamba, Léopold; Sahut, Jean‐Michel; Braune, Eric; Teulon, Frédéric
Abstract: The objective of this study is to examine the relationship between a company's environmental performance and its systematic risk. Using a sample of 351 European listed companies over the 2007–2015 period, the technique of principal components analysis is applied to calculate a synthetic global index of corporate environmental performance using 71 evaluation criteria suggested by the ASSET4 database. Using this same approach, subindices of the global index are calculated using the following ASSET4 dimensions: reduction of emissions, product innovation, and reduction of resource usage. To test the relationship between these variables and risk, panel data regression techniques are applied. Results indicate that the synthetic global index of environmental performance negatively affects the systematic risk of company. The decomposition of this global index into three subindices shows that those subindices relating to the reduction of environmental emissions and of resource usage make it possible to significantly reduce systematic risk, whereas the subindex relating to product innovation has a rather moderate effect. Thus, environmental performance, like governance, can be considered as an insurance mechanism for the company, which reduces the probability of events occurring, which negatively affect its cash flow and risks faced by shareholders.